Glochidion malingheense (Phyllanthaceae), a new species from Guizhou, China - Yao, Gang; Liu, Zengcai; Lang, Yuanxing; Liao, Desheng; Xu, Junbo; Luo, Shixiao; Deng, Chaoyi (Phytotaxa, 2022)
Glochidion malingheense, a new species from southwestern Guizhou, China, is described. Morphologically, the new species is most similar to G. oblatum Hook. f. in having angled branchlets, leathery leaves, and thick pericarp of capsules that become lignified to some extent when dry, but clearly differs from the latter by its long pedicelled pistillate flowers that are with oblong sepals, short cylindrical styles, depressed globose ovary, subcircular to broadly ellipticum sepals of staminate flowers, 3 stamens and smaller fruits.